Ethics and doping - Parry, J. (1999)
Paper on the IEC Doping Conference, Barcelona, 17 - 18 june 1999 "The limits of sport: doping". There are six parts to this paper. The first is negative, since I try to show how some popular arguments against doping do not work. The second looks, conversely, at arguments against a ban on doping. The third highlights a positive feature of the debate, which I believe is not often noticed, and which has serious consequences. The fourth presents a thought experiment in order to reveal those foundational values of sport threatened by doping practice. The fifth looks again at the `unfair advantage` argument, and the sixth returns to a consideration of why doping should be banned.